Copernicus Climate Change Service, Climate reanalysis - European Centre for Medium-Range Weather Forecasts (ECMWF) (European Centre for Medium-Range Weather Forecasts (ECMWF), 2020)
Climate reanalyses combine past observations with models to generate consistent time series of multiple climate variables. Reanalyses are among the most-used datasets in the geophysical sciences. They provide a comprehensive description of the observed climate as it has evolved during recent decades, on 3D grids at sub-daily intervals.

Klimatreanalyser kombinerar tidigare observationer med modeller för att generera konsekventa tidsserier av flera klimatvariabler. Reanalyser är bland de mest använda dataseten inom geofysiska vetenskaper. De ger en omfattande beskrivning av det observerade klimatet som det har utvecklats under de senaste decennierna, på 3D-nät med dagliga intervaller.
Copernicus Climate Change Service, Klimatreanalyser
Keywords: climate change; klimatförändringar; ATMOSPHERIC TEMPERATURE; LAND SURFACE; LAND SURFACE TEMPERATURE; CLIMATE INDICATORS; LAND SURFACE MODELS; air temperature; lufttemperatur; temperature; temperatur; weather forecasting; global climate; modelling; land surface temperature; SMHI; SMHI; Climate Science; Klimatvetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi